Perceived Autobiographical Coherence Predicts Depressive Symptoms Over Time Through Positive Self–Concept - Hallford, David John; Ricarte, Jorge Javier; Hermans, Dirk (Frontiers in Psychology, 2021)
The coherence of autobiographical memories plays an important role in psychological well-being, as borne out by recent studies. This study aimed to advance this understanding by assessing whether coherence predicted depressive symptoms over time in adults. Further, it aimed to specify mediators through which this association might occur, namely psychological resources of self-esteem self-efficacy, meaning in life, and optimism. A sample of 160 participants (M age = 26.4, SD = 3.2, 58.1% women) completed surveys at three time-points spaced one week apart. The surveys contained measures of the perceived coherence of autobiographical memories, psychological resources, and depressive symptoms. The results of a path analysis model, controlling for depressive symptoms at baseline, indicated that only causal coherence predicted later depressive symptoms, and that this occurred through positive self-concept, represented by self-esteem and self-efficacy. Limitations of the study include no examination of cultural background as a moderating factor and the short time-intervals. Overall, the findings provide further evidence that the perception of how events have unfolded and impacted on one’s life and sense of self is particularly important in mitigating depressive symptoms. It extends on our understanding by showing this occurs through changes in self-concept.